The Issues of Measuring the Exterior and Interior Noise of Road Vehicles - Sarkan, Branislav; Stopka, Ondrej; Li, Chenguang (Communications - Scientific letters of the University of Zilina, 2017)
Nowadays, within the issues of road vehicles operation, we place great emphasis especially on the most important operating characteristics such as fuel consumption, exhaust emissions as well as performance indicators. However, in the field of driving comfort, a noise inside the vehicle, affecting its crew, represents an important aspect as well. The paper analyzes the interior and exterior vehicle noise, methods of its detection and practical research measurement indicating the rate of interior vehicle noise during various traffic conditions.